The Influence Of Job Satisfaction And Work Motivation On Teacher Performance At Public Senior High School 9 Medan - Silvia Sofyan; Ferry Hidayat; Robin Robin; Dina Wulandari (Pusat Riset dan Inovasi Nasional, 2024)
The research carried out identified the influence between independent (free) variables and dependent (bound) variables, where the independent (free) variables were job satisfaction (X1) and work motivation (X2) and the dependent (bound) variable was teacher performance. (Y). The research results show that partially job satisfaction and work motivation have a partial positive and significant influence on teacher performance at Public Senior High School 9 Medan schools. Furthermore, simultaneously job satisfaction and work motivation have a significant influence on teacher performance at Public Senior High School 9 Medan. The advice that can be given in this research is that all teachers at Public Senior High School 9 Medan must work well, and get motivation from the senior teachers there so that they can work better.